2, 4‐Dichlorophenol induces DNA damage through ROS accumulation and GSH depletion in goldfish Carassius auratus. (9th August 2018) - Huang, Dejun; Zhang, Xiaoning; Zhang, Chen; Li, Hui; Li, Dong; Hu, Yan; Yang, Feng; Qi, Yongmei
Abstract : 2, 4‐Dichlorophenol (2, 4‐DCP) is one of the most abundant chlorophenols in the aquatic environment and has been frequently detected in surface waters. Although ecological and cellular toxicity of 2, 4‐DCP has aroused the public concern, few reports focus on the genotoxicity, especially on DNA double strand breaks (DSBs), of 2, 4‐DCP in fish. The present study aims to explore the genotoxic effect of 2, 4‐DCP on DSBs in goldfish Carassius auratus and to further elucidate its potential mechanism. The results showed that 2, 4‐DCP significantly induced DSBs (detected by neutral comet assay) in erythrocytes and hepatocytes of goldfish in a dose‐dependent manner, indicating a genotoxicity of 2, 4‐DCP on fish. The total antioxidant capability and the content of reduced glutathione (GSH) were significantly decreased, while the level of reactive oxygen species (ROS) was significantly increased in a dose‐dependent manner in erythrocytes and hepatocytes, suggesting an oxidative stress caused by 2, 4‐DCP in fish. N‐acetyl‐l ‐cysteine, a precursor of GSH and a ROS scavenger, significantly impaired 2, 4‐DCP‐induced ROS overproduction and DSBs, which proves that ROS accumulation and GSH depletion are involved in 2, 4‐DCP‐induced DNA damage in fish. Environ. Mol. Mutagen. 59:798–9, 2018. © 2018 Wiley Periodicals, Inc.